2021
DOI: 10.1002/bmc.5151
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic comparisons of six steroid saponins in rat plasma following oral administration of crude and stir‐fried Fructus Tribuli extracts by UHPLC–MS/MS

Abstract: Modern pharmacological studies have shown that Fructus Tribuli can improve sexual function and treat cardiovascular diseases. In this study, we focused on comparing the pharmacokinetics of crude Fructus Tribuli (CFT) and stir-fried Fructus Tribuli (SFT) to further clarify the changes in chemical composition in vivo. The quantitation of six analytes was performed in a triple quadrupole mass spectrometer using the multiple reaction monitoring mode. Separation was performed on a Halo ® C 18 column using 0.05% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The content of Terrestrosin K, Terrestrosin D, and other steroidal saponins in RFT and SFT has been estimated previously via the UHPLC‐MS/MS technique, which indicated their measurability 18,21 . The pharmacokinetics of Terrestrosin K and Terrestrosin D has also been investigated via in vivo experiments in rats 27,36–38 . However, considering the current state of research on RFT and SFT and production and development of reference standards of FT, Terrestrosin D and Terrestrosin K are the best choices that can meet the Q‐marker requirements at this stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of Terrestrosin K, Terrestrosin D, and other steroidal saponins in RFT and SFT has been estimated previously via the UHPLC‐MS/MS technique, which indicated their measurability 18,21 . The pharmacokinetics of Terrestrosin K and Terrestrosin D has also been investigated via in vivo experiments in rats 27,36–38 . However, considering the current state of research on RFT and SFT and production and development of reference standards of FT, Terrestrosin D and Terrestrosin K are the best choices that can meet the Q‐marker requirements at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…18,21 The pharmacokinetics of Terrestrosin K and Terrestrosin D has also been investigated via in vivo experiments in rats. 27,[36][37][38] However, considering the current state of research on RFT and SFT and production and development of reference standards of FT, Terrestrosin D and Terrestrosin K are the best choices that can meet the Q-marker requirements at this stage. Therefore, given the conclusions of previous studies and considering the "five principles" of Q-marker research, it was initially concluded that Terrestrosin D is an RFT Q-marker and Terrestrosin K is an SFT Q-marker.…”
Section: Selection Of Potential Q-markersmentioning
confidence: 99%